Influence of stabilisers on the unconfined compressive strength of a fine soil - Feng, Mingwei; Liu, Shu; Wang, Juan; Hu, Yunfeng (ICE Publishing, 2020)
In foundation engineering, weak subgrade soils are usually improved by adding several stabilisers to satisfy construction requirements, but the influence degree of each stabiliser on the strength of the stabilised soils is rarely studied. In this study, a series of unconfined compressive strength tests was conducted on a fine soil stabilised with various proportions of cement, lime, fly ash and gypsum. The influences of the four stabilisers were investigated through quantitative analysis and grey correlation analysis. The quantitative analysis examined the trends of the unconfined compressive strength with increasing contents of different stabilisers. It was found that there existed optimum fly ash and gypsum contents in this study. Also, the cement had the highest positive impact on the unconfined compressive strength. In the grey relational analysis, different normalisation methods were utilised, and it was found that the normalisation method and the trend of the strength with rising stabiliser content affected the order of the impact of various stabilisers. The grey relational analysis with a range-normalisation method provided a reasonable order of impact in this study.